2001
DOI: 10.1023/a:1012982626401
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Leptin is a 16 kDa protein that exerts important effects on the regulation of food intake and energy expenditure by interacting with the leptin receptor in the brain and in many other tissues. Although leptin is produced mainly by white adipose tissue, several laboratories have shown low levels of leptin production by a growing number of tissues including the anterior pituitary gland. Many studies have implicated leptin in anterior pituitary function including the observation that homozygous mutations of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 150 publications
0
26
0
Order By: Relevance
“…2). Previous studies have indicated that STAT3 activation through tyrosine phosphorylation plays an important role in leptin signal transduction at the pituitary gland (Tsumanuma et al 2000, Lloyd et al 2001. Although pituitary cells other than thyrotropes also express leptin receptors (Sone et al 2001), our findings suggest that reduced leptin signalling in the whole pituitary gland might contribute to the abolishment of the direct effect of leptin on TSH secretion from the isolated pituitaries of the hypothyroid rats that were previously studied (Da Veiga et al 2004).…”
Section: Discussionmentioning
confidence: 52%
“…2). Previous studies have indicated that STAT3 activation through tyrosine phosphorylation plays an important role in leptin signal transduction at the pituitary gland (Tsumanuma et al 2000, Lloyd et al 2001. Although pituitary cells other than thyrotropes also express leptin receptors (Sone et al 2001), our findings suggest that reduced leptin signalling in the whole pituitary gland might contribute to the abolishment of the direct effect of leptin on TSH secretion from the isolated pituitaries of the hypothyroid rats that were previously studied (Da Veiga et al 2004).…”
Section: Discussionmentioning
confidence: 52%
“…This proved to be correct for rat and human pituitary and brain and several groups confirmed and extended these findings [17, 18, 19]. High levels of leptin mRNA were also found in a human neuroblastoma cell line [20].…”
Section: Introductionmentioning
confidence: 66%
“…It has been speculated that leptin and GH directly interact (28,31). Some of the GH cells in the pituitary contain leptin granules and have leptin receptors (31,47). Moreover, homozygous mutations of the leptin receptor gene lead to decreased GH secretion (47).…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary radiation and pituitary surgery itself may change hypothalamic ghrelin and leptin sensitivity as the GH secretagogue receptor (GHSR) on which ghrelin binds is also located in the hypothalamus (48), and leptin granules and receptors were detected in GH cells of the pituitary (31,47). …”
Section: Discussionmentioning
confidence: 99%